Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1073/pnas.92.10.4616
|View full text |Cite
|
Sign up to set email alerts
|

Role of sodium and potassium ions in regulation of glucose metabolism in cultured astroglia.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
161
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 48 publications
15
161
1
1
Order By: Relevance
“…It is widely reported that neurons in vitro consume more glucose than cultured astroglia (Brookes and Yarowsky, 1985;Itoh et al, 2003b;Takahashi et al, 1995). Therefore, we did not compare the glucose phosphorylation rate between neurons and astroglia in vitro with 2-NBDG in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely reported that neurons in vitro consume more glucose than cultured astroglia (Brookes and Yarowsky, 1985;Itoh et al, 2003b;Takahashi et al, 1995). Therefore, we did not compare the glucose phosphorylation rate between neurons and astroglia in vitro with 2-NBDG in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of oxidative phosphorylation for EPSC recovery after a strong presynaptic stimulus could implicate the astrocyte-neuron lactate shuttle (Pellerin and Magistretti, 1994;Takahashi et al, 1995;Bittner et al, 2010). However, neither pharmacological inhibition of monocarboxylate transport (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If half of the glucose is metabolized in astrocytes, then increased oxidative metabolism produces a similar amount of ATP as the increase in glycolysis. If all glycolytic ATP were used to Brain lactate metabolism GA Dienel +15 to +180 +40 to +55 Pellerin and Magistretti, 1994;Takahashi et al, 1995;Debernardi et al, 1999;Chatton et al, 2003 10-1,000…”
Section: Brain Activation In Vivo Activates Glycogenolysis and Oxidatmentioning
confidence: 99%